RELEVANSI PENDIDIKAN ISLAM PADA MASA UMAR BIN KHATAB DENGAN APLIKASI PENDIDIKAN ISLAM KONTEMPORER - Rahma Yanti; Maghfirah Insannia; Wedra Aprison (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This research examines the implementation of Islamic education during the time of Umar bin Khattab and its relevance to contemporary Islamic education. In this research, the author is interested in discussing education during the time of Umar bin Khattab, because Caliph Umar was a person who made it possible for Islamic education to advance and spread to other countries. Umar's relatively long reign of 10 years had an impact on the expansion of Islamic territory beyond the Arabian Peninsula. This means that the spread of Islam at that time was increasingly widespread, considering these conditions, Caliph Umar also emphasized the issue of Islamic education. This type of research is literary research that uses analytical methods using a social history approach and uses books, articles and journals related to the caliph Umar bin Khattab with the relevance of Islamic education during the time of Umar bin Khattab to contemporary Islamic education and its application. The results of this research show that from an educational perspective, during Umar bin Khattab's time, teacher recruitment already had qualifications in accordance with the educational qualifications of educators. The educational methods used during Umar bin Khattab's time were halaqah, talaqi, and lectures. And these methods are still relevant to current educational methods. This shows the relevance between Islamic education today and Islamic education during the time of Umar bin Khattab. And currently the application of educational values carried out by Caliph Umar Bin Khatab has been carried out. And education today is more sophisticated, because it is influenced by technological developments.